PATTERN OF CAUSES AND MANAGEMENT OF PERMANENT LOSS OF VOICE STUDIED AT A TERTIARY CARE HOSPITAL - Wahid, Fazal i (Journal of Postgraduate Medical Institute, 2013)
Objective: To determine the frequency of causes of hoarseness leading to permanent loss of voice anddiscuss their management. Methodology: This descriptive study was carried out at the department of ENT, Head and Neck Surgery,Lady Reading Hospital Peshawar from January 2009 to December 2011. All these patients were evaluatedin terms of detailed history, thorough examination and relevant investigations. Biopsy from laryngeal masswas taken in case of tumours. Total laryngectomy was performed in patients with advanced laryngealtumours provided with preoperative counseling regarding postoperative handicaps. The patients withlaryngeal narrowing due to trauma were subjected to laryngeal stenting. The data was analyzed usingSPSS 15. Results: Out of 16 patients 10 were male and 6 were female with male: female ratio of 1.6:1. The agesranged from 09-75 years with mean age of 43.68 + S.D 18.65 years. Majority of patients (68.75%) hadlow socioeconomic status. Main presentation of these patients was hoarseness (100%). The commonestcause of change of voice was laryngeal carcinoma (n-6, 37.5%), followed by blast injury (25%).Endolaryngeal stenting was the commonest (43.75%) procedure performed for traumatic laryngeal stenosisfollowed by total laryngectomy. Most of the patients gained good esophageal speech. Conclusion: It is concluded that beside laryngeal cancer, trauma to the larynx is a common cause ofpermanent loss of voice resulting due to increased incidence of violence in our set up. Esophageal speechcan be easily and successfully instituted in laryngectomized patients among other voice rehabilitativeoptions.